A nurse practitioner–led care bundle approach for primary care of patients with complex health needs. Issue 2 (21st February 2022) - Christianson-Silva, Paula; Russell-Kibble, Audrey; Shaver, Joan
ABSTRACT: Background: Often developed for acute care and less frequently for primary care, care bundles are clusters of evidence-based practices for improving care delivery and patient outcomes. Care bundles usually arise when ineffective or costly outcomes are identified, are meant to make care more reliable, and require superb teamwork and communication. Local problem: Patients using the highest proportion of health care services are those living with complex health conditions and challenging sociocultural lives, statistics corroborated within our primary care clinic. In our nurse practitioner (NP)-led, interprofessional, team-based primary care program serving mainly low-income patients, we noted that many patients with multiple chronic conditions had an excess of clinic encounters, emergency department visits, and hospitalizations. Methods: To improve health status for these patients and reduce costly care inefficiencies, we developed a unique bundle of care practices for embedding within our NP-led complex care program. Our goals were to improve patient efficacy for self-management of chronic conditions and promote appropriate use of health care resources and services. Interventions: Using AEIØOU as a mnemonic, the derived care bundle better focused our team efforts and provided us with a planning, communication, and documentation schema for quality improvement. It was particularly useful for team-based care because tasks could be documented or communicated by letter or number and easily reviewed by team members or others involved in patients' care. Results: Use of the AEIØOU bundle within our program resulted in better coordination of team-based comprehensive care for our high-needs patients, seen anecdotally in fewer unnecessary contacts and missed appointments and in patient appreciation comments. Emergency department visits and hospitalization data for the six months before compared with 6 months after enrollment in the program showed significant reductions. Conclusions: To improve the primary care of complex patient populations, we recommend further use and testing of the AEIØOU bundle within other care models.